Hijacking a bacterial ABC transporter for genetic code expansion - Tarun Iype; Maximilian Fottner; Paul Böhm; Carlos Piedrafita; Yannis Möller; Michael Groll; Kathrin Lang (Nature, 2025)
Abstract The site-specific encoding of non-canonical amino acids (ncAAs) provides a powerful tool for expanding the functional repertoire of proteins 1–4 . Its widespread use for basic research and biotechnological applications is, however, hampered by the low efficiencies of current ncAA incorporation strategies. Here we reveal poor cellular ncAA uptake as a main obstacle to efficient genetic code expansion and overcome this bottleneck by hijacking a bacterial ATP-binding cassette (ABC) transporter 5 to actively import easily synthesizable isopeptide-linked tripeptides that are processed into ncAAs within the cell. Using this approach, we enable efficient encoding of a variety of previously inaccessible ncAAs, decorating proteins with bioorthogonal 6 and crosslinker 7 moieties, post-translational modifications 8,9 and functionalities for chemoenzymatic conjugation. We then devise a high-throughput directed evolution platform to engineer tailored transporter systems for the import of ncAAs that were historically refractory to efficient uptake. Customized Escherichia coli strains expressing these evolved transporters facilitate single and multi-site ncAA incorporation with wild-type efficiencies. Additionally, we adapt the tripeptide scaffolds for the co-transport of two different ncAAs, enabling their efficient dual incorporation. Collectively, our study demonstrates that engineering of uptake systems is a powerful strategy for programmable import of chemically diverse building blocks.